Research classification: Principles and applications for health research - Mukti, Bayu Hari; Mahdiyah, Dede (Health Sciences International Journal, 2026)
Background: Health research plays a crucial role in generating evidence that supports clinical practice, policy development, and public health interventions. The diversity of research types—ranging from descriptive to experimental studies—reflects the complexity of health problems and the need for appropriate methodological approaches. Objective: This review aims to provide a comprehensive overview of the classifications of health research, emphasizing their characteristics, purposes, strengths, and limitations, as well as factors that determine the choice of research design. Discussion: Health research can be classified based on purpose, design, approach, time, and population. Basic research contributes to fundamental scientific knowledge, while applied, evaluative, and developmental studies bridge theory with practical solutions. Quantitative approaches allow generalization of findings, qualitative approaches capture cultural and social meanings, and mixed methods integrate both dimensions to offer a holistic perspective. By design, studies can be descriptive, analytic observational, experimental, quasi-experimental, case studies, or action research, each serving specific contexts and questions. The choice of design is influenced by research questions, available resources, validity requirements, ethical considerations, and socio-cultural characteristics of the population. Conclusion: Understanding the diversity of health research designs is essential for producing reliable and relevant evidence. A careful selection of methods ensures that research not only contributes to scientific knowledge but also provides practical implications for improving health outcomes and informing policy decisions.